منهج مقترح لتعليم اللغة العربية من خلال الكلمات الإندونيسية ذات أصل عربي في قاموس المنور للمبتدئين - Silvia Mulyani; Syirojul Huda (Rayah Al-Islam, 2020)
Language is a life and culture. The Muslim should learn Arabic because it is the language of the Qur'an and because it carries Islamic culture. The Indonesian speaking who learn Arabic, they do not start from zero. They actually have some basic from the Arabic loan words that exist in Indonesian. Al-Munawwir is the largest Arabic-Indonesian dictionary and the most widely used in Indonesian. And in education world, methods plays a very important role to help learning process. This study aimed at determining the Arabic loan words in Al-Munawwir Dictionary (from letter B to H) and the proposed method to learn Arabic by using those words for beginner students. The research used descriptive analysis method. The result of this study were: In Al-Munawwir Dictionary (from letter B to H), there were some Arabic loan words as many as 206 words. This study also illustrated a proposed method for learning Arabic using those words. The method describes four elements of the curriculum and applied them in dialogues, texts and exercises.